New Insights about Upwelling Trends off the Portuguese Coast: An ERA5 Dataset Analysis - Spallou Ferreira; Magda Sousa; Ana Picado; Nuno Vaz; João Miguel Dias (Journal of Marine Science and Engineering, 2022)
In recent decades, several studies have highlighted the importance of the temporal and spatial structure of upwelling in defining the high levels of productivity of coastal upwelling systems. This work intends to assess the temporal and spatial trends of upwelling along the west and south Portuguese coasts from 1979 to 2020, comparing the patterns between these regions. Two different methodologies to calculate the upwelling indexes (UI), based on wind and sea surface temperature (SST) data, were applied to relate the wind-induced upwelling-favourable conditions (UIET) with the expected response on superficial waters, as indicated by the SST patterns (UISST). The upwelling-favourable conditions are quite consistent and more frequent and intense on the west coast than on the south coast. Spatially, it was verified from the UIET that upwelling-favourable conditions are more intense in association with the main west coast capes and that there is an intensification of favourable winds towards Cape São Vicente, both on the west and south coasts. Seasonally, upwelling-favourable UIET was found to be more consistent in the summer on both coasts. However, it also exists in the winter months. In terms of interannual variations, it should be highlighted that between 1992 and 2005 more intense favourable conditions and an apparent change in the seasonality after 2015 were found. Although some of the results derived from the UIET are corroborated by the UISST (namely, the main spatial trends and interannual variations in the upwelling intensity), several uncertainties are associated with the last index that interfere with its interpretation. For future works, it is advisable to develop a more robust SST-based index that can circumvent the uncertainties pointed out in the present study.